Rice husk-derived nano-SiO2 assembled on reduced graphene oxide distributed on conductive flexible polyaniline frameworks towards high-performance lithium-ion batteries. Issue 23 (16th May 2022) - Ratsameetammajak, Natthakan; Autthawong, Thanapat; Chairuangsri, Torranin; Kurata, Hiroki; Yu, Ai-shui; Sarakonsri, Thapanee
Abstract : By combining rice husk-derived nano-silica and reduced graphene oxide and then polymerizing PANI by in situ polymerization, we created polyaniline-coated rice husk-derived nano-silica@reduced graphene oxide composites with excellent electrochemical performance. Abstract : By combining rice husk-derived nano-silica and reduced graphene oxide and then polymerizing PANI by in situ polymerization, we created polyaniline-coated rice husk-derived nano-silica@reduced graphene oxide (PANI-SiO2 @rGO) composites with excellent electrochemical performance. ATR-FTIR and XRD analyses confirm the formation of PANI-SiO2 @rGO, implying that SiO2 @rGO served as a template in the formation of composites. The morphology of PANI-SiO2 @rGO was characterized by SEM, HRTEM, and STEM, in which SiO2 nanoparticles were homogeneously loaded on graphene sheets and the PANI fibrous network uniformly covers the SiO2 @rGO composites. The structure can withstand the large volume change as well as retain electronic conductivity during Li-ion insertion/extraction. Over 400 cycles, the assembled composite retains a high reversible specific capacity of 680 mA h g −1 at a current density of 0.4 A g −1, whereas the SiO2 @rGO retains only 414 mA h g −1 at 0.4 A g −1 after 215 cycles. The enhanced electrochemical performance of PANI-SiO2 @rGO was a result of the dual protection provided by the PANI flexible layer and graphene sheets. PANI-SiO2 @rGO composites may pave the way for the development of advanced anode materials for high-performance lithium-ion batteries.